Low-cost, lightweight IoT platform with custom LPWAN LoRa integration - Santos, André Daniel Lopes dos (2020)
In this thesis, we present our IoT platform developed by using open source technologies, following a flexible component approach. The platform architecture is divided into multiple layers providing the flexibility required in order to allow the integration of custom gateways and application servers. The proposed IoT platform supports Low Power Wide Area Networks (LPWAN) integration, such as LoRa, using a custom network server implementation. The network server supports uplink/downlink communications with a Message Queuing Telemetry Transport (MQTT) interface. This work may be applied in remote places, for example, in rural areas in order to support the deployment of IoT solutions. To support multiple IoT enabled devices through different network types, a multi-protocol approach is intended for the proposed platform. The main goal of our research is to provide a low-cost, lightweight, multi-protocol, as a custom LoRa implementation alternative, that supports, IoT applications, gateways, devices, and their respective sensors/actuators.